Willingness to pay for high-quality remote radiation oncology training in Latin America. (January 2022) - Li, Benjamin; Perez, Thomas; Hao, Jinxuan; Rodriguez, Diego; Oladeru, Oluwadamilola; Castaneda, Serguei A.; Sarria, Gustavo R.
Graphical abstract: Highlights: Willingness to pay acts as a surrogate for perceived value of services. Most practitioners in Latin America are willing to receive remote training. Mainly, less-experienced professionals would cover their own educational expenses. Abstract: Access to high-quality continuing medical education, particularly in Radiation Oncology, can be challenging in some developing countries due to economic barriers. Despite the current offer of free-access self-educational material, end user training faces a backlog still difficult to overcome. The purpose of this investigation is to report the willingness-to-pay profile of practitioners in Latin America, as a surrogate of quality perception of remote educational resources. Related factors include professional experience and baseline practice confidence levels. Most of practitioners would cover their own expenses, while an increased tendency in less-experienced professionals was observed. However, baseline knowledge confidence levels were not influential in decision making. This report contributes to better know the profile of Latin American professionals, in order to design future educational interventions in the region and bridging the current accessibility gap.